2020
DOI: 10.1590/1413-7054202044020119
|View full text |Cite
|
Sign up to set email alerts
|

Does the substrate affect the germination of soybean seeds treated with phytosanitary products?

Abstract: The use of an appropriate method that accurately expresses physiological seed quality and minimizes possible phytotoxicity by chemical products in laboratory testing with soybean seeds is relevant. The objective of this work was to evaluate the influence and infer the method adequacy for the representative evaluation of physiological quality of soybean seeds treated with phytosanitary products. Two experiments were carried out in a completely randomized design, with trial 1 in a 9×5 factorial scheme involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 18 publications
1
26
0
1
Order By: Relevance
“…Nevertheless, regardless of the time of application, the germination test showed that seeds treated with the insecticides Cropstar®, Cruiser®, and Pirâmide® had a lower percentage of normal seedlings than the seeds treated with the other products, which confirms that some insecticide molecules can show toxicity in physiological analyses, especially in a paper substrate (Brzezinski et al, 2015;Ferreira et al, 2016;Santos et al, 2018). Rocha et al (2020) observed that the treatments of soybean seeds with insecticide molecules affect germination and seedling evaluation, with greater phytotoxicity in relation to fungicide molecules, especially in analysis methods with abundant and readily available water.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Nevertheless, regardless of the time of application, the germination test showed that seeds treated with the insecticides Cropstar®, Cruiser®, and Pirâmide® had a lower percentage of normal seedlings than the seeds treated with the other products, which confirms that some insecticide molecules can show toxicity in physiological analyses, especially in a paper substrate (Brzezinski et al, 2015;Ferreira et al, 2016;Santos et al, 2018). Rocha et al (2020) observed that the treatments of soybean seeds with insecticide molecules affect germination and seedling evaluation, with greater phytotoxicity in relation to fungicide molecules, especially in analysis methods with abundant and readily available water.…”
Section: Resultsmentioning
confidence: 86%
“…Germination under water restriction (GH): performed according to the method described above for the germination test; however, an aqueous solution containing mannitol (P.A C6H14O6 -M.W. 182.17) was used to moisten the germination paper for artificial simulation of water restriction and to obtain osmotic potential of -0.25 MPa (Rocha et al, 2020). Four (4) replicates of 50 seeds were used for each block.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Del Bem Junior et al ( 2020) also observed lower physiological quality after storage in soybean seeds treated with the insecticide thiamethoxam. According to Rocha et al (2020), insecticidal molecules hinder soybean germination and may cause greater seed phytotoxicity than fungicides.…”
Section: Resultsmentioning
confidence: 99%
“…Physiological quality must be maintained until sowing, so the period between seed field production and sowing, i.e., storage, is relevant. During storage, several factors are important, including environmental conditions (Smaniotto et al, 2014), genotype (Carvalho et al, 2014a), and the composition and volume of solution in the treatment (Santos et al, 2018), especially when insecticidal molecules that have a greater tendency for toxicity than fungicides are used (Rocha et al, 2020). Monitoring the time that the soybean seed can remain treated without impairing its physiological quality, the "seed safety", is extremely important (Carvalho et al, 2020).…”
Section: Introductionmentioning
confidence: 99%